An expressive syntax is in informative texts of political subjects (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article talked about the concept of expressivity in informative text. The value of expressivity opens up as to the linguistic category. Material is characterized from positions of syntax, the structural is taken into account and semantic aspects.
Keywords: expressiveness; expressive syntax; phrase